Bees (Hymenoptera: Apoidea) of Gorgona Natural National Park, Colombian Pacific - González-Cordoba, Marcela; Montoya-Lerma, James (Revista de Biología Tropical, 2014)
The National Natural Park Gorgona is a continental island off the Colombian Pacific coast. Bees have a specialized and crucial role in this isolated and unique ecosystem and here we assess their biodiversity. In three visits, at intervals of three months, six areas of the island with variable vegetation cover, were sampled. Sampling was done indirectly using (i) McPhail traps (baited with cineole, methyl silicate and clove oil), (ii) Van Someren Rydon traps (baited with rotting fish, chicken or fruit), (iii) Malaise traps and (iv) light traps. In addition, a direct sampling was carried out along transects of indeterminate length, for periods of one hour in each area and repeated four times. A total of 585 specimens was captured, of these 443 belong to Apidae (14 genera), 141 to Halictidae (six genera) and one Megachilidae. With this report the local inventory of bees rises to 43 species and 28 genera. Trigona fulviventris guianae Cockerell, 1910 was the most abundant species, Euglossa ignita, the most attracted to aromatic lures and Megalopta genalis Meade-Waldo, 1916 was the dominant species during evening hours. The absence of Apis mellifera was noticeable. Rev. Biol. Trop. 62 (Suppl. 1): 297-305. Epub 2014 February 01.